Guide to load analysis for durability in vehicle engineering - Johannesson, Par; Speckert, Michael (Chichester, West Sussex : Wiley., 2013)
"Covers the use of established computational methods, such as finite element method (FEM) and multi body simulation (MBS), and their appropriate use within load analysis for durability"--
pt. I. Overview -- pt. II. Methods for load analysis -- pt. III. Load analysis in view of the vehicle design process.
Includes bibliographical references and index.
Print version record and CIP data provided by publisher.
Keywords: Trucks -- Dynamics; Finite element method; Trucks -- Design and construction; TECHNOLOGY & ENGINEERING -- Automotive; Finite element method; Trucks -- Design and construction; Trucks -- Dynamics; TECHNOLOGY & ENGINEERING / Automotive; Electronic books; Electronic books; Electronic books